Optimization of the circular microchannel heat sink under viscous heating effect using entropy generation minimization method. (October 2019) - Chauhan, Prathvi Raj; Kumar, Rajan; Bharj, Rabinder Singh
Highlights: Numerical study carries out the optimization of channel dimensions. Viscous heating effects are considered in this study. Entropy generation due to fluid heat conduction in the radial and the axial directions is examined. Entropy generation due to fluid friction is significant towards the micro dimension. Abstract: The present numerical study carries out the optimization of the channel dimension ( DN corresponding to N -number of channels) under the consideration of viscous heating effects in entropy generation (EG) through a uniformly heated microchannel heat sink (MCHS). The numerical computations are performed for a constant total mass flow rate m ̇ tot and constant total heat flow rate q ̇ tot . In EG formulation, the partial differential equations (PDEs) are discretized by the first-order forward difference method and the temperature in the denominator is taken as the local one. The EG due to fluid friction ( Sgen, FR ) and heat conduction ( Sgen, HT ) individually as well as simultaneously is also reported. The EG due to fluid heat conduction in the radial ( Sgen, HT-rad ) and axial ( Sgen, HT-ax ) directions are also examined. The results indicate that the frictional entropy generation ( Sgen, FR ) is significant towards the micro dimensions of the channel. Additionally, the optimum diameter ( D* ) corresponding to the optimum number ( N* ) of the channels is designed at minimum total EG ( Sgen, tot ).